Cost of human resources from a behavioral perspective - حمود, سعد علي; جياد, علي رزاق (Journal of Economics and Administrative Sciences, 2011)
Purpose/objective:1 - To explain the financial impact of the activities and areas of human resources management and the adoption of the methodology for estimating costs on the basis of conduct and statement of how to assess costs and benefits of human resource activities.2 - Measuring  human capital, and its impact on the financial statements. Design/methodology/approach: Concentrated dimensions of the research paper's lack of financial statements prepared by the organizations for information mandated human resource its components of the three (attraction - development - released), as well as the financial impact in the conduct of the organization will have the reader able to understand the pressure, the cost to the policies of human resource, as well as that understanding of awareness of behavioral financial issue in itself, should be addressed in order to find some kind of mental and intellectual relations about what that directs the behavior of the investor. Findings:The information about the cost of human resources, can increase the efficiency of the management staff, by helping to make sound decisions in the field of polarization, the selection and appointment, development, transport, upgrade, use, calendar, and bonuses related to them. Moreover, the financial statements based on cost (accounting) human capital, so that hurt the main purpose of disclosure and identification of related items.